Millimeter-Wave Underlay D2D Communications: Channel Assignment, Transmission mode Selection and Power Control for Full-CSI and Limited-CSI Scenarios - Nima Reisi (مهندسی مخابرات جنوب)
In this paper, we study relay-assisted underlay D2D communication operating at millimeter-wave (mmWave) band in which half-duplex/full-duplex relays may assist D2D users to improve transmission quality. Our aim is to jointly select D2D transmission mode, assign cellular resource blocks to D2D users and control the powers of users in order to maximize the aggregate data rate of the D2D users and cellular network. We focus on the main features of mmWave communication including larger bandwidth, directive antenna arrays at BS and users, and more severe path loss and shadowing. As the optimization problem is mixed-integer-non-linear programming, two heuristic algorithms are proposed, assuming full Channel Side Information (CSI) and limited CSI at Base Station, respectively. Simulation results show the superiority of utilizing FD relays over HD relays and direct transmission, especially for non-line-of-sight links, which is the dominant propagation mechanism in mmWave band. The limited CSI algorithm has considerably lower complexity. Moreover, when the number of resource blocks far exceeds the number of D2D users, the gap between full CSI and limited CSI algorithms vanishes.